REDESAIN INTERIOR BUTIK GAUN CLEMENTINE COUTURE SURABAYA DENGAN KONSEP SIMPLE ENCHANTING - Jesseline Carissa Novita; Tresiyani Mettasari Liesawan (LPPM Institut Desain dan Bisnis Bali, 2021)
Abstract. Clementine Couture Boutique would be redesigned into a custom and rental gown boutique that attracts customers amidst the COVID-19 pandemic. Other than the health protocol, there are problems that require to be solved. The problems are the hazy brand identity, vague circulation, and lack of facility. Not only displaying rows of beautiful dresses, for the customers, the concept